2020
DOI: 10.3892/etm.2020.8641
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ranibizumab combined with photodynamic therapy on wet age‑related macular degeneration

Abstract: Efficacy and safety of intravitreal ranibizumab (IVR) combined with photodynamic therapy (PDT) in treating wet age-related macular degeneration (wAMD) were studied. A total of 130 eyes were collected from 130 wAMD patients treated in Affiliated to Qingdao University Yuhuangding Hospital of Yantai, of which 65 were given IVR combined with PDT (combination therapy group) and the remaining 65 were treated with simple IVR (ranibizumab group). The differences in best corrected visual acuity (BCVA), central macular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In the TAP study, progression of dominant classical lesions was observed. In the 24month follow-up, lesion size was smaller than 6 MPS-DA in 55% of patients in verteporfin group, while this rate was 25% in placebo group (19). VIP study, the progression of the classical component of the lesion was 45% less in the verteporfin group than in the placebo group in the 24-month follow-up.…”
Section: Discussionmentioning
confidence: 83%
“…In the TAP study, progression of dominant classical lesions was observed. In the 24month follow-up, lesion size was smaller than 6 MPS-DA in 55% of patients in verteporfin group, while this rate was 25% in placebo group (19). VIP study, the progression of the classical component of the lesion was 45% less in the verteporfin group than in the placebo group in the 24-month follow-up.…”
Section: Discussionmentioning
confidence: 83%
“…Chen et al (2020) [ 118 ] described the advantages in combination therapies of ranibizumab with PDT, such as the increase in visual acuity and decrease in central macular thickness when compared with ranibizumab monotherapy in AMD patients. Existent CNV was blocked by PDT, and ranibizumab injections are capable of resisting VEGF and repressing CNV, and consequently, the clinical efficiency of combined therapies is strengthened [ 118 ]. However, other studies also demonstrate no significant difference in visual acuity outcome when comparing ranibizumab monotherapy and combined therapy with PDT for wet AMD [ 119 , 120 ].…”
Section: Exudative Age-related Macular Degeneration (Wet Amd)mentioning
confidence: 99%